Participatory on-farm evaluation of wheat genotypes - Pandey, Deepak; Chaudhari, Hemant Kumar; Upadhyay, Shesh Raman; Gautam, Nutan Raj; Ghimire, Bhakti Ram; Shrestha, Jiban; Thapa, Dhruba Bahadur (Journal of Agriculture and Natural Resources, 2019)
In wheat development programs, the evaluation and identification of superior genotypes is the first and leading step in a crop improvement program. Coordinated Farmer’s Field Trial (CFFT) was conducted during the three successive wheat growing season of 2010/11, 2011/12 and 2012/13. In CFFT six different wheat genotypes were planted in different outreach sites of research stations of Nepal Agricultural Research Council (NARC) at varying geographical regions. CFFT was conducted according to standard recommended practices of wheat at farmers’ field with different sets of genotypes for Terai and hill. In CFFT for Terai Tar and Lower valley (TTL) under timely sown irrigated (TSI) condition wheat genotype NL 1073 produced the grain yield of 3695 kg/ha and under the timely sown rainfed (TSR) that was 2738 kg/ha in 2010/11. In 2011/12, wheat genotype NL 1073 had the highest recorded grain yield of 3691 kg/ha in mid western region which was followed by check variety Vijay in CFFT-TTL in 2011/12 in the same region. Similarly in 2012/13, check variety Vijay showed the highest grain yield of 3818 kg/ha and 3044 kg/ha followed by NL 1094 (2938 kg/ha and 3468 kg/ha) in TSR and TSI environments, respectively. In CFFT for Mid and High Hill (MHH) WK 1204 had the highest grain yield of 3967 kg/ha in TSI which was followed by NL 1008 with the yield of 3890 in 2010/11. In 2011/12 the highest mean grain yield was observed in WK 1204 (4242 kg/ha) followed by BL 3872 (3922 kg/ha). Similarly, in 2012/13 NL 1008 was the best genotypes on the basis of grain yield (3297 kg/ha) followed by NL 1055 (3131 kg/ha) under CFFT-MHH.